Averting Evolutionary Suicide from the Tragedy of the Commons. Issue 1 (11th November 2021) - Lansing, John Stephen; Chung, Ning Ning; Chew, Lock Yue; Jacobs, Guy S.
In a tragedy of the commons, individual competition over a resource can reduce the resource itself, and thus reduce the fitness of the whole group. An extreme example is evolutionary suicide, which is predicted to occur when the selfish interests of free-riders and cheaters overwhelm cooperative behaviors, and the social good on which they depend ceases to exist. Case studies cite many different and seemingly interacting factors for success. Here we propose an equation-based theoretical model to predict changes in this balance, which determine whether the tragedy of the commons is observed in a particular scenario. Using survey data from 20 Balinese subaks, we explore the explanatory power of two theoretical traditions that are currently used to analyze commons management institutions, revealing multiple regimes with correlated responses to environmental threats. To explore case studies from a comparative perspective requires both theory and methods that can account for differences between regimes and explore transitions between them.